Elastic critical moment for bisymmetric steel profiles and its sensitivity by the finite difference method - Kamiński, Marcin; Supeł, Łukasz (Zielona Góra: Uniwersytet Zielonogórski)
It is widely known that lateral-torsional buckling of a member under bending and warping restraints of its cross-sections in the steel structures are crucial for estimation of their safety and durability. Although engineering codes for steel and aluminum structures support the designer with the additional analytical expressions depending even on the boundary conditions and internal forces diagrams, one may apply alternatively the traditional Finite Element or Finite Difference Methods (FEM, FDM) to determine the so-called critical moment representing this phenomenon.
Keywords: critical moment; finite difference method; sensitivity analysis; thin walled structures; FiniteElement Method